Improving Hospital Pharmacy Service Quality Using Lean Management Principles - Sembiring, Grace Faskarina; Saragi, Sahat; Amyulianthy, Rafrini (Sciences of Pharmacy, 2025)
Efficient pharmaceutical services are vital to hospital care quality. This study addresses process inefficiencies at RSIA Viola Bekasi’s pharmacy, including SOP non-compliance, long wait times, and poor stock management. Using a qualitative descriptive approach, observations, interviews, and secondary data, Lean Management was implemented collaboratively with hospital leadership. Pre-intervention, compounded prescriptions averaged 30–45 min; non-compounded, 15–20 min. Post-intervention, times dropped to 20.17 and 6.5 min respectively, improving efficiency by 33%–68%. Lean practices also reduced waste, improved flow, and optimized inventory through JIT and FEFO systems. Results show Lean Management effectively enhances pharmacy operations, service quality, and patient satisfaction, offering practical evidence for its application in Indonesian maternal and child healthcare settings.